THE STUDENTS’ PERCEPTION ON THE USE OF “DEEPL TRANSLATION TOOL” FOR READING COMPREHENSION AT FKIP UNIVERSITAS RIAU - Salsabila, Khoirul Ana; Erni, Erni; Azhar, Fadly (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2024)
Abstract: This study aimed to find out how students use ofDeepL TranslationTool as reading comprehension at FKIP Universitas Riau. Random sampling techniquewas applied to decide the sample. There were 40 students as the participants. Theinstrument used was a questionnaire categorized into 3 components of perception onthe use of DeepL Translation such as absorption, understanding, and evaluation. Thefindings indicated the score of percentage was more than 60%. It means students’perception towards DeepL Translate was in high category. This result showed that theuse of DeepL is easier, faster, and sound natural than other translation tools. The firstindicator, absorption got the highest percentage was a high category. There were threestatements getting very high category and seven statements get high category. Thesecond indicator students’ level in understanding was in a high category. There weretwo statements get very high category, five statements get high category, and threestatements get medium category. And the last, for this indicator, students’ level inevaluation was in a high category. There were two statements getting very highcategory and eight statements get high category.Key Words: Perception, DEEPL Translation, Reading Comprehension